The mathematics of options trading. - Reehl, C. B., ....- (New York : McGraw-Hill, 2005)
The Mathematics of Options Trading shows options traders how to improve their overall trading performance by first understanding and harnessing options mathematics. This detailed manual introduces the math needed to understand options and how they work and provides step-by-step instructions on how to use that math to analyze intended trades before committing capital. Traders learn how to use moving averages, curve fitting, extreme values, skewness, and other techniques to augment trading profits. The valuable accompanying CD-ROM contains programs for analyzing opportunities using several strategies, creating spreadsheets, and more.
Keywords: Handel